The value of language skills - Gilles Grenier; Weiguo Zhang (IZA World of Labor, 2021)
In today's globalized world, people are increasingly mobile and often need to communicate across different languages. Learning a new language is an investment in human capital. Migrants must learn the language of their destination country, but even non-migrants must often learn other languages if their work involves communicating with foreigners. Economic studies have shown that fluency in a dominant language is important to economic success and increases economic efficiency. However, maintaining linguistic diversity also has value since language is also an expression of people's culture.
Keywords: J15; J18; J26; J61; H41; 330; language; human capital; immigration; lingua franca; English; linguistic diversity